Cultivation of Socio-Religious Attitudes Through A participatory Approach in Muslim Society - Ainal Mardhiah; Zulfatmi; Zubaidah; Yuni Setia Ningsih; M. Chalis (Bansigom Na Publisher, 2024)
Abstract In Muslim societies, building social cohesion and religious values is an important priority. This study aims to explore how participatory approaches can be used to enhance social-religious attitudes in Muslim societies. Communities are involved from identifying problems to feeling the benefits together. This process begins with empowering communities through capacity development related to social characteristics, which then changes community behaviour related to waste reduction and involvement in its management. The results show that the presence of public facilities such as mosques can be a catalyst for the development of social bonds among citizens. Religious activities in the mosques, such as cleansing, can also strengthen silaturahim among the members of the community. In addition, public spaces such as playgrounds can be an arena for children to sharpen their social skills by meeting and interacting with children from different backgrounds